The matching method for treatment evaluation with selective participation and ineligibles - Monica Costa Dias; Hidehiko Ichimura; Gerard J. van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2008)
The matching method for treatment evaluation does not balance selective unobserved differences between treated and non-treated. We derive a simple correction term if there is an instrument that shifts the treatment probability to zero in specific cases. Policies with eligibility restrictions, where treatment is impossible if some variable exceeds a certain value, provide a natural application. In an empirical analysis, we first examine the performance of matching versus regression-discontinuity estimation in the sharp age-discontinuity design of the NDYP job search assistance program for young unemployed in the UK. Next, we exploit the age eligibility restriction in the Swedish Youth Practice subsidized work program for young unemployed, where compliance is imperfect among the young. Adjusting the matching estimator for selectivity changes the results towards ineffectiveness of subsidized work in moving individuals into employment.
Keywords: J64; C14; C25; 330; propensity score; policy evaluation; treatment effect; regression discontinuity; selection; job search assistance; subsidized work; youth unemployment; Arbeitsmarktpolitik; Arbeitslosigkeit; Jugendarbeitslosigkeit; Matching; Großbritannien; Schweden